Draft genome sequence of Lactobacillus plantarum CRL1506, an immunomodulatory strain isolated from goat milk - Saavedra, Maria Lucila (2016)
This report describes a draft genome sequence of Lactobacillus plantarum CRL1506, a probiotic strain with immunomodulatory properties isolated from goat milk. The reads generated by a whole-genome shotgun (WGS) strategy on an Illumina MiSeq sequencer were assembled into contigs with a total size of 3,228,096 bp. The draft genome sequence of L. plantarum CRL1506 will be useful for further studies of specific genetic features of this strain and for understanding the mechanisms of its immunobiotic properties.